Avoidance of noninfectious sternal dehiscence: figure-of-8 wiring is superior to straight wire closure. (August 2013) - Almdahl, Sven M.; Halvorsen, Per; Veel, Terje; Rynning, Stein E.
Abstract: Objectives . Comparison of figure-of-8 wiring or simple straight-wiring technique assessed by the frequency of early noninfectious sternal dehiscence. Design . Observational register study with 7835 patients having sternal closure with figure-of-8 steel wires was compared with 2122 patients, where the sternotomy was closed by simple interrupted straight wires. The endpoint was the rate of early (within 30 days) sterile sternal dehiscence. Results . Fourteen patients (0.66%) with single wires and five patients (0.06%) with figure-of-8 wires underwent re-operation for nonmicrobial sternal disruption (p < 0.0001). The median time-point for re-intervention was 6 days for both groups. In more than 6000 patients, the sternotomy was closed with five figure-of-8 wires without dehiscence in any of them. Conclusion . In a large cohort of consecutive cardiac operations, it was found that sternal closure with figure-of-8 wires is better than closure with simple interrupted wires.